Modified 2D Viterbi Algorithm using 2D Modulation Encoding Constraints in BPMR Systems - Sokjabok, Siwakon; Warisarn, Chanon; Koonkarnkhai, Santi; Lee, Jaejin (My University, 2020)
The severity of inter-symbol interference (ISI) and inter-track interference (ITI) effects caused by the reduction of the spacing between bit islands in the along- and across-track directions to acquire ultra-high areal densities (ADs) is the main problem in bit-patterned magnetic recording (BPMR) systems. We call these two effects as two-dimensional (2D) interference, which can degrade the overall system performance. Practically, a one-dimensional (1D) modulation code, e.g., run-length limited (RLL) code, is essentially utilized to prevent the severe ISI effect. The use of 2D detectors is also one of the important ways to cope with the severe ITI; however, its complexity is quite high. To avoid the severe ITI effect and complex 2D detectors; therefore, we propose to apply the 1D RLL code as the 2D modulation code. Then, the 2D modulation encoding constraint is employed to reduce the number of states and branches in the trellis of the proposed modified 2D Viterbi detector. Simulation results reveal that the proposed detector not only delivers a lower complexity but also provides superior bit error rate gain, especially at ultra-high ADs and/or large location fluctuation.
Keywords: 2D modulation code; 2D Viterbi detector; Bit-patterned magnetic recording (BPMR); Run-length limited code